A simulation model for long-term analysis of the electricity market - Or, İlhan; Paşaoğlu Kılanç, Güzay (European Council Modelling & Simulation, School Computing & Mathematics, Nottingham Trent Univ, Burton Street, Nottingham, Ng1 4Bu, England, 2006)
After the liberalization of the electricity generation industry, capacity expansion decisions are made by multiple self-oriented power companies. Unlike the regulated environment, decision-making of market participants is now guided by price signal feedbacks and by an imperfect foresight of the future market conditions that they will face. In such an environment, decision makers need to understand long-term dynamics of the supply and demand side of the power market. To visualize the competitive electricity power market dynamics, a simulation model based on system dynamic philosophy is developed in this study. The developed model includes the demand module, the capacity expansion module, the power generation sector, an accounting and financial module, various competitors and a bidding mechanism (power pooling system). By means of such a decision tool, companies and regulators have a better opportunity to understand possible consequences of different decisions that they may make under different policies and market conditions. The main part of the paper is devoted to a detailed presentation of the model. At the end, some findings of the preliminary scenario analysis are discussed.
Keywords: electricity market; system dynamic; simulation